Susceptibility of mammalian cell line for isolation of IBDV from clinical samples - Silva,SEL (2004)
Susceptibility of chicken embryo related cells (CER) to non-classical IBDV was compared with Vero cells for the same purpose. It was used 20 bursal samples collected from clinical cases of IBDV, positive by histopathological evaluation. After three times infection of CER and Vero cells monolayers, at 6, 12, 18, 24, 48, 60 and 72h post-infection (PI), extra-cellular and intracelluar IBDV was measured. The extra-cellular amount of IBDV particles was quantified by DAS-ELISA from 6h PI, and increased for both cells studied until 72h PI. The IBDV re-isolation performed by infecting chicken embryos showed positive results at all PI studied. The intracellular IBDV RNA was shown by RT-PCR, where all tested samples were positive. However, the cytopathic effect (CPE) caused by IBDV infection was pronounced at 18h for Vero and 36h for CER cells. The RT-PCR was done to detect IBDV RNA from the bursa samples, where all were positive. Regarding to IBDV isolation, 20% of samples tested were negative in Vero cells, where all were positive in CER cells infection. The findings allow concluding that CER cell can be a new and appropriated tool for IBDV isolation.